THE EFFECT OF REACT TYPE LEARNING MODEL ON STUDENTS' LEARNING OUTCOMES IN WAJO SOUTH SULAWESI - Ermi Sola; Andi Kastina (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
His study aims to determine the learning outcomes of grade X science students at SMA Negeri 9 Wajo who were taught using the REACT learning model in physics. Knowing the learning outcomes of grade X science students at SMA Negeri 9 Wajo who were not taught to use the REACT learning model in physics learning. And it was knowing the effect of the application of the REACT type learning model on the learning outcomes of class X science students at SMA Negeri 9 Wajo. The research design used was The Posttest-Only Control Group Design. The population in this study were all students of class X IPA SMA Negeri 9 Wajo for the academic year 2019/2020, totaling 88 people spread over three classes. The research sample came from classes X IPA 2 and X IPA 3, each of which amounted to 33 people. Sampling was carried out using the Simple Random Sampling technique. The instrument used in this study was a learning outcome test. The data analysis technique used was descriptive analysis and simple regression analysis. The results of the descriptive research show that (1) the average value of the learning outcomes of class X IPA 1 students who were taught using REACT type learning was 89.85. (2) the average value of student learning outcomes that were not taught with REACT type learning was 77.87. (3) There was a significant effect on student learning outcomes. It can be seen in the output value obtained with a coefficient of determination (R Square) of 0.532, which means that there was an influence of the independent variable (Application of the REACT Type Learning Model) on the dependent variable (Participant Learning Outcomes) by 53.2%. Therefore, the application of the REACT learning model has a significant effect on student learning outcomes. The implication of this research was learning using the REACT learning model (Relating, Experiencing, Applying, Cooperating, Transfering) was able to encourage students to be active in the learning process and will affect student learning outcomes.